Pelatihan Bisnis Rintisan Mahasiswa Melalui Research dan Design Thinking - Pusvita Yuana; Aulia Azzardina (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2024)
ABSTRACTDuring the Covid-19 pandemic, the number of MSMEs in Indonesia has decreased and weakened. The increase in the number of MSMEs will affect the economy in a positive way. Therefore, the government encourages increasing the number of young entrepreneurs to help grow the national economy. This is also the concern of universities to become a source of strengthening and developing productive entrepreneurship among young people. It is essential to train students in research and design thinking because young entrepreneurs who start businesses need assistance in advancing their business knowledge. Community service activities are carried out in collaboration with the Melusinau Community which actively provides learning opportunities in various fields and shares experiences with experts. Activities will be carried out in three meetings for two weeks using the zoom application. On the first day of the meeting delivered material on design thinking introduction and user understanding, the second day was concept generation and prototyping, and the third day was sample presentation and pitching tips. Through this community service activity, it is expected that each activity carried out can increase student knowledge and strong basic abilities to minimize the risk of failure. Based on the results of the evaluation of the implementation of the activities of the participants, 80.26% of the participants gave very satisfying results and 19.74% of the participants were satisfied during the workshop.ABSTRAKSelama pandemi Covid-19, jumlah UMKM di Indonesia mengalami penurunan dan melemah. Padahal dengan meningkatnya UMKM, perekonomian di Indonesia juga akan mengalami peningkatan. Oleh karena itu, pemerintah mendorong peningkatan jumlah wirausaha muda guna membantu pertumbuhan ekonomi nasional. Hal ini juga menjadi perhatian perguruan tinggi untuk menjadi sumber penguatan dan pengembangan wirausaha produktif dari kalangan anak muda. Dikarenakan wirausaha muda yang merintis bisnis memerlukan bantuan untuk memperkuat dasar pengetahuan bisnis, sehingga pelatihan kepada mahasiswa mengenai Research dan Design Thinking melalui kegiatan pengabdian kepada masyarakat perlu untuk dilakukan. Kegiatan pengabdian kepada masyarakat dilaksanakan dengan melakukan kerjasama dengan Komunitas Melusinau yang secara aktif memberikan kesempatan belajar pada beragam bidang dan berbagi pengalaman dari para pakar. Pelaksanaan kegiatan sebanyak tiga kali pertemuan dalam dua minggu dan menggunakan aplikasi zoom. Pada pertemuan hari pertama menyampaikan materi tentang design thinking introduction and understanding user, hari kedua yaitu concept generation and prototyping, dan hari ketiga yaitu presentation sample and pitching tips. Melalui kegiatan pengabdian kepada masyarakat ini diharapkan dari masing-masing kegiatan yang dijalankan dapat memberikan peningkatan baik pada pengetahuan mahasiswa maupun kemampuan dasar yang kuat sehingga mahasiswa dapat meminimalkan terjadinya risiko kegagalan. Berdasarkan hasil evaluasi pelaksanaan kegiatan dari peserta, 80,26% peserta memberikan hasil yang sangat puas dan 19,74% dari peserta merasa puas selama berlangsungnya workshop.